2021
DOI: 10.4269/ajtmh.21-0586
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Recent SARS-CoV-2 Infection on the Course and Severity of Dengue in Children: A Prospective Observational Study from North India

Abstract: In 2020, a considerable overlap occurred between the COVID-19 pandemic and seasonal dengue transmission in India. This study aimed to evaluate the effects of acute or recent infection with SARS-CoV-2 on the course and outcomes of dengue fever in children. We prospectively enrolled 44 children with a clinical and laboratory diagnosis of dengue fever. Assessment of acute and recent SARS-CoV-2 infection was done using reverse transcription–polymerase chain reaction and IgG antibody through ELISA. Children were gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…It was found that previous exposure to SARS-CoV-2 had resulted in a less severe outcome with no death ( Ravikumar et al , 2021 ). These observations serve as further circumstantial/epidemiological evidence of our observations that SARS-CoV-2 serum samples can neutralize and protect against dengue.…”
Section: Discussionsupporting
confidence: 75%
“…It was found that previous exposure to SARS-CoV-2 had resulted in a less severe outcome with no death ( Ravikumar et al , 2021 ). These observations serve as further circumstantial/epidemiological evidence of our observations that SARS-CoV-2 serum samples can neutralize and protect against dengue.…”
Section: Discussionsupporting
confidence: 75%
“…A recent study showed that previous SARS-CoV-2 infection may increase the risk of severe dengue ( 39 ). However, dengue fever might follow a less severe course, has also been found in children with recent SARS-CoV-2 infection ( 40 ). In these children, a trend toward a lower incidence of acute kidney injury and fewer organ dysfunctions has been reported.…”
Section: Discussionmentioning
confidence: 97%
“…Due to the cross‐reactivity of these Abs, when the same cohort is being exposed to SARS‐CoV‐2, partial neutralization seemed to occur and as a result the spread, as well as the severity of COVID‐19 in these people, appears to be reduced. Similarly, as observed in neutralization assays, there are reports stating reduced incidences of dengue in the post‐pandemic era or less severe dengue infection with a previous history of SARS‐CoV‐2 infection 71 …”
Section: Cross‐reactivity and Cross‐protection Indeed Exist Between D...mentioning
confidence: 60%